Evidence of Increase in Mortality After the Introduction of Diphtheria–Tetanus–Pertussis Vaccine to Children Aged 6–35 Months in Guinea-Bissau: A Time for Reflection? - Aaby, Peter; Mogensen, Søren Wengel; Rodrigues, Amabelia; Benn, Christine S. (Frontiers in Public Health, 2018)
Background: Whole-cell diphtheria-tetanus-pertussis (DTP) and oral polio vaccine (OPV) were introduced to children in Guinea-Bissau in 1981. We previously reported that DTP in the target age group from 3-5 months of age was associated with higher overall mortality. DTP and OPV were also given to older children and in the present study we tested the effect on mortality in children aged 6-35 months. Methods: In the 1980s, the suburb Bandim in the capital of Guinea-Bissau was followed with demographic surveillance and tri-monthly weighing sessions for children under 3 years of age. From June 1981, routine vaccinations were offered at the weighing sessions. We calculated mortality hazard ratio (HR) for DTP-vaccinated and DTP-unvaccinated children aged 6-35 months using Cox proportional hazard models. Including the present study, the introduction of DTP vaccine and child mortality has been studied in three studies; we made a meta-estimate of these studies. Results: At the first weighing session after the introduction of vaccines, 6-35 month old children who received DTP-vaccination had better weight-for-age z-scores (WAZ) than children who did not receive DTP; one unit increase in WAZ was associated with an odds ratio of 1.32 (95% CI=1.13-1.55) for receiving DTP-vaccination. Though lower mortality compared with not being DTP-vaccinated was therefore expected, DTP-vaccination was associated with a non-significant trend in the opposite direction, the HR being 2.22 (0.82-6.04) adjusted for WAZ. In a sensitivity analysis including all children weighed at least once before the vaccination program started, DTP (+/-OPV) as the most recent vaccination compared with live vaccines or no vaccine was associated with a HR of 1.89 (1.00-3.55). In the three studies of the introduction of DTP in rural and urban Guinea-Bissau, DTP vaccinated children had an HR of 2.14 (1.42-3.23) compared with DTP-unvaccinated children; this effect was separately significant for girls (HR=2.60 (1.57-4.32)) but not for boys (HR=1.71 (0.99-2.93)) (test for interaction p = 0.27). Conclusions: Although having better nutritional status and being protected against three infections, 6-35 months old DTP-vaccinated children tended to have higher mortality than DTP-unvaccinated children. All studies of the introduction of DTP have found increased overall mortality.